Solvothermal synthesis and crystal structure of aqua-tris(p-acetamidobenzoate-κ2O,O′)-(2,2′-bipyridine-κ2N,N′)terbium(III) - water - methanol (1/1/1) - Xu Zhuo-Wen; Xia Yu-Xuan; Li Chang-Hong; Li Wei; Liu Yang (Zeitschrift für Kristallographie - New Crystal Structures, 2024)
C75H76N10O23Tb2, triclinic, P−1‾ $P-\overline{1}$ (no. 2), a = 10.4524(13) Å, b = 12.9626(16) Å, c = 15.2003(18) Å, α = 108.674(2)∘, β = 94.931(2)∘, γ = 101.617(2)∘, V = 1885.8(4) nm3, Z = 1, R gt(F) = 0.0236, wR ref(F 2) = 0.0584, T = 296 K.